Establishment Of Callus And Cell Suspension Cultures Of Artemisia Annua L. Of Mongolian Origin For The Production Of Artemisinin - Khaw, Mei Lin (2021)
Artemisia annua L., a medicinal plant used for centuries to treat a broad range of diseases because of its natural compound, artemisinin. However, the content of artemisinin in the plant is low, about 0.01-1.4 % of its dry weight, depending on the plant variety and subjected to environmental factors. Thus, A. annua L. plant originated from Mongolian was studied to explore a new source of plant variety as a source of artemisinin. The present study reported an optimised protocol to produce in vitro plants, induce callus, and establish the cell suspension culture of A. annua L. to produce artemisinin.